The effect of dietary Aloe vera powder on growth performance and survival rate of Oreochromis niloticus fries - Jared J Ochingo; Mercy Chepkirui; Vivian Kemunto (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2023)
This study aimed to evaluate the impact of dietary Aloe vera on the growth performance parameters of Oreochromis niloticus fry. A feeding trial was conducted for a month at KMFRI Sang'oro Aquaculture station and 135 fish were randomly assigned to three treatments, including a Control group (C1), a group fed with 1% Aloe vera (A1), and a group fed with 2% Aloe vera (B1). The growth parameters, including Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), Weight Gain (WG), and Survival were measured. The results indicated that the administration of Aloe vera at different concentrations significantly improved the growth performance of fish. The SGR, FCR, and WG were significantly higher in fish fed with Diet B (2% Aloe vera) followed by those fed with Diet A (1% Aloe vera) compared to the Control group. The results confirmed the Alternative hypothesis that there is a significant difference in the growth performance of fish fed with various incorporations of Aloe vera. Therefore, the study recommends the use of Aloe vera as a growth promoter in aquaculture, particularly at higher incorporation rates of 2%.